International Relations: India, Russia, and the US Swing forward the Future of Geopolitics “Modi's US Visit: What New Delhi Wants from Washington”. - Mukesh Kumar Mishra (ZBW – Leibniz Information Centre for Economics, 2023)
India's engagement with the United States is driven by a combination of strategic, economic, and shared values considerations. New Delhi would seek to leverage and balance its relationship with Washington also to advance its national interests, enhance its security, and promote its economic growth and development.
Keywords: F52; F53; F55; 330; Geopolitics; International Relations